Comparing the infection biology and gene expression differences of Plasmodiophora brassicae primary and secondary zoospores - Yang, Hui; Sun, Qianyu; Zhang, Yihan; Zhang, Yang; Zhao, Yushan; Wang, Xinyue; Chen, Yanmei; Yuan, Shu; Du, Junbo; Wang, Wenming (Frontiers in Microbiology, 2022)
Plasmodiophora brassicae (Wor.) is an obligate plant pathogen affecting Brassicae worldwide. To date, there is very little information available on the biology and molecular basis of P. brassicae primary and secondary zoospore infections. To examine their roles, we investigated the differences between samples inoculated separately with resting spores and secondary zoospores. The obvious development of P. brassicae asynchrony that is characterized by secondary plasmodium, resting sporangial plasmodium and resting spores was observed at 12 days in Brassica rapa inoculated with resting spores but not when inoculated with secondary zoospores at the same time. Inoculation with resting spores resulted in much more development of zoosporangia clusters than inoculation with secondary zoospores in nonhost Spinacia oleracea. The results indicated that primary zoospore infection played an important role in the subsequent development. To improve our understanding of the infection mechanisms, RNA-seq analysis was performed. Among eighteen effectors identified in P. brassicae, thirteen effectors were induced in B. rapa seedlings inoculated with resting spores, which suggested that the pathogen and host first contacted, and more effectors were needed. Corresponding to those in B. rapa, the expression levels of most genes involved in the calcium-mediated signaling pathway and PTI pathway were higher in plants inoculated with resting spores than in those inoculated with secondary zoospores. The ETI pathway was suppressed after inoculation with secondary zoospores. The genes induced after inoculation with resting spores were suppressed in B. rapa seedlings inoculated with secondary zoospores, which might be important to allow a fully compatible interaction and contribute to a susceptible reaction in the host at the subsequent infection stage.